Development of a food preservative from sea buckthorn together with chitosan: Application in and characterization of fresh-cut lettuce storage - Feng, Kexin; Feng, Xiaolin; Tan, Weijian; Zheng, Qinhua; Zhong, Wenting; Liao, Caiyu; Liu, Yuntong; Li, Shangjian; Hu, Wenzhong (Frontiers in Microbiology, 2023)
The purpose was to create a compound food preservative for fresh-cut lettuce utilizing chitosan and flavonoids from sea buckthorn leaf (FSL). The FSL-1 was extracted and purified from the Sea buckthorn leaves (SBL). Analysis was done on the impact of purified FSL-1 concentration on the physicochemical characteristics of the compound preservative, including its capability to form films, its antioxidant capacity, and its ability to prevent bacterial growth. It was used to assess the physicochemical indices of fresh-cut lettuce throughout storage. To further investigate the impact of the compound preservative on fresh-cut lettuce, different FSL-1 concentrations of the preservative were applied to the surface. Changes in weight loss, hardness, browning index, total chlorophyll content, SOD, and MDA were then analyzed. According to the results of Fourier transform infrared spectroscopy, FSL-1 interacted with chitosan and FCCP-2, which had the maximum viscosity (6.88mPa·s) and increased the contact angle of flavonoid from sea buckthorn leaf and chitosan compound preservative (FCCP) on both horizontal glass and polystyrene plates as the concentration of FSL-1 increased (0–2 mg/mL). With the diameter of the antibacterial circle of S. aureus, E. coli, S. typhimurium, and L. monocytogenes being (21.39 ± 0.22) mm, (17.43 ± 0.24) mm, (15.30 ± 0.12) mm, and (14.43 ± 0.24) mm, respectively. It was demonstrated that as the concentration of FSL-1 increased, the antibacterial activity became stronger. The compound preservative showed the optimum scavenging action against ferric-reducing antioxidant power, DPPH radicals (96.64%), and ABTS radicals (99.42%) when FSL-1 was added at 2 mg/mL. When FCCP-2 with FSL-1 concentration of 1 mg/mL was used to coat fresh-cut lettuce during the same storage time, various indices such as weight loss, hardness, browning index, SOD activity, and MDA content of lettuce were better than those of other test groups. This was true even when the lettuce was stored at 4°C for 7 days. A novel form of FCCP has a significant promise for quality and extended shelf life in food security since it is a natural food preservative with better antibacterial and antioxidant capabilities.